Verkehr und Siedlungsstruktur — eine dynamische Gestaltungsaufgabe - Holz-Rau, Christian (Raumforschung und Raumordnung | Spatial Research and Planning, 2001)
The success of transport planning and transport policy in the endeavour to bring about sustainable development with regard to transport and traffic has to be seen as no more than limited. Discussion has been focused on structural factors (transport infrastructure, settlement structure, fuel tax, etc.) which in many cases are not implementable (punitively high petrol prices) and/or which are not capable of achieving the envisaged effects to the degree desired (functional mix). Today’s transport structures and the current state of development of transportation are the result of “sovereign decision-making” (e.g. in the preparatory land-use plans (zoning plans) of local authorities), and of the “decisions of individual citizens” (e.g. in choosing where to live and the mode of transport they use). Accordingly, planning concepts need to be augmented by an “individualised” component and geared more to those existing assets which will dominate in the long term.
Keywords: Article